2021
DOI: 10.3389/fbioe.2021.639070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shear Stress on Production of FVIII and vWF in a Cell-Based Therapeutic for Hemophilia A

Abstract: Microfluidic technology enables recapitulation of organ-level physiology to answer pertinent questions regarding biological systems that otherwise would remain unanswered. We have previously reported on the development of a novel product consisting of human placental cells (PLC) engineered to overexpress a therapeutic factor VIII (FVIII) transgene, mcoET3 (PLC-mcoET3), to treat Hemophilia A (HA). Here, microfluidic devices were manufactured to model the physiological shear stress in liver sinusoids, where infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…While the low levels of mRNA for the fVIII transgene argue that ER stress was not likely the cause of low secreted FVIII activity, the upregulation of ER stress is obviously not desirable, as it will likely negatively impact the viability and functionality of the PLCs, precluding their use in cell therapy. The upregulation of TLR 3 and TLR 7 by the plasmids would also likely compromise one of the key attributes of PLCs for use as an off-the-shelf therapy, namely, their state of relative immune-inertness, a conclusion supported by our recent report showing activation of PLCs leads to production of γ-IFN ( 68 ). As such, another lucrative avenue for future studies would be the redesign of the plasmids to remove any bacterial sequences that might be serving as pathogen-associated molecular patterns (PAMPs) and be responsible for recognition by the TLRs within the PLCs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…While the low levels of mRNA for the fVIII transgene argue that ER stress was not likely the cause of low secreted FVIII activity, the upregulation of ER stress is obviously not desirable, as it will likely negatively impact the viability and functionality of the PLCs, precluding their use in cell therapy. The upregulation of TLR 3 and TLR 7 by the plasmids would also likely compromise one of the key attributes of PLCs for use as an off-the-shelf therapy, namely, their state of relative immune-inertness, a conclusion supported by our recent report showing activation of PLCs leads to production of γ-IFN ( 68 ). As such, another lucrative avenue for future studies would be the redesign of the plasmids to remove any bacterial sequences that might be serving as pathogen-associated molecular patterns (PAMPs) and be responsible for recognition by the TLRs within the PLCs.…”
Section: Discussionmentioning
confidence: 85%
“…This is especially true for the hLSECs, which exhibit very slow division kinetics and cannot be propagated for more than a couple of passages in vitro prior to senescing. The PLCs employed in the present study exhibit a phenotype and biological properties that closely resemble that of MSC from other tissues ( 3 , 22 , 68 ). It is noteworthy that prior studies have reported the downregulation of components of the DNA damage response (DDR) and HRR pathways in MSC with time in culture ( 94 96 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…200 ng of RNA was converted into cDNA using the RT 2 First Strand Kit (Qiagen, Valencia, CA, United States). SYBR Green-based qPCR was performed using the qRT-PCR Primer Assay (Qiagen, Valencia, CA, United States) with the following human primers: (1) human fVIII (qRT-F8-FWD: 5′-ATGCACAGCATCAATGGCTAT-3′, qRT-F8-REV: 5′-GTGAGTGTGTCTTCATAGAC-3′) and (2) human vWF (qRT-vWF-FWD: 5′-GGATTCAGTGGATGCAGCAG-3′, qRT-vWF-REV: 5′-TAGGGAGGTCTTCGATTCGC-3′) ( Trevisan et al, 2021 ). Commercially available primers for Human GAPDH were used as an internal reference housekeeping gene (Qiagen, Valencia, CA, United States).…”
Section: Methodsmentioning
confidence: 99%